Infection and Risk of Gastric Cancer in Korea: A Quantitative Systematic Review - Jong-Myon Bae; Eun Hee Kim (Korean Society for Preventive Medicine, 2016)
Objectives: In the context of the global decrease in mortality due to gastric cancer, previous studies have reported that the effect of chronic Helicobacter pylori (H. pylori) infection on the incidence of gastric cancer varies among regions. This systematic review was conducted to investigate H. pylori as a risk factor for gastric cancer in Korea, where the incidence of gastric cancer is among the highest in the world. Methods: A search strategy was established to identify articles published in Korean as well as in English. Ultimately, we included observational studies conducted among Korean patients that designed with an age-matched and sex-matched control group that reported the odds ratio associated with H. pylori. Gastric cancer cases were subdivided into overall (OGC), cardia (CGC), non-cardia (NGC), early (EGC), advanced, intestinal (IGC), and diffuse forms of gastric cancer. Summary odds ratios (SORs) with 95% confidence intervals (CIs) were calculated in the meta-analysis using a random-effect model. Results: Eleven case-control studies were ultimately selected. H. pylori was associated with an SOR of 1.81 (95% CI, 1.29 to 2.54) for OGC. Additionally, statistically significant risks were observed for CGC, NGC, EGC, and IGC. Conclusions: Chronic H. pylori infection was found to raise the risk of gastric cancer among Koreans, with the highest risk observed for CGC and EGC (SOR=2.88 for both). Follow-up clinical epidemiologic studies are needed to assess the effects of current treatments aimed at eradicating H. pylori infections.